Application of project management tool in construction for Planning, Scheduling and Optimization. (2023) - Shah, Parth; Chandragade, Anushree A.
Abstract: In India, the number of building construction projects is increasing, with growth expected to reach double digits in Fiscal Year 2022, up from an 8.6 % decrease last year. Time and cost overruns, on the other hand, are important issues in the construction sector due to poor planning. The goal of this study is to determine the impact of typical construction flaws and scheduling errors on construction time and expense overruns. In the present work, the scheduling and estimation of G + 11 building at Pune, Maharashtra has been performed on available project planning software (Microsoft Project (MSP2010) and Wrike). Microsoft Project (MSP) and Wrike software are promoted as excellent project management tools. MSP is a technique for reducing time and expense overruns via proper planning and scheduling. Wrike is used to plan and organize the building project. Implementation of these planning software is not only results in reduction of construction cost but also allows reduction in construction duration.